PERAN CUSTOMER EXPERIENCE DALAM MEMEDIASI PENGARUH OMNICHANNEL DIGITAL MARKETING TERHADAP CUSTOMER LOYALTY PADA UMKM DI KOTA SUKABUMI - Agus Sobar; Rizky Maulana; Sandi Setiadi (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to examine the mediating role ofcustomer experience in the relationship between omnichannel digital marketing and customer loyalty among Micro, Small, and Medium Enterprises (MSMEs) in Sukabumi City, Indonesia. The research employed a quantitative explanatory approach involving 150 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the SmartPLS software. The findings indicate that omnichannel digital marketing has a positive and significant effect on both customer experience and customer loyalty. Furthermore, customer experience positively influences customer loyalty and serves as a significant mediating variable in the relationship between omnichannel digital marketing and customer loyalty. These results suggest that the effectiveness of omnichannel marketing strategies in fostering long-term customer loyalty depends on the ability of MSMEs to deliver satisfying and consistent customer experiences across multiple marketing channels. The study highlights the importance of integrating digital marketing channels to enhance customer engagement and strengthen customer loyalty in the MSME sector.